Gambaran Kesesuaian Peresepan Obat Pasien BPJS Rawat Jalan Dengan Formularium Nasional - Herty Nur Tanty; Siti Aisyah; Ida Diana; Anissa Nandya Kirana (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2023)
The hospital formulary is a list of drugs agreed upon by medical staff, compiled by the pharmacy and therapy committee set by the hospital director. With the formulary, pharmaceutical installations can provide drugs more efficiently and the drugs listed in the formulary must be guaranteed its availability. If a hospital does not have a hospital formulary, it will have an impact on the number of types of drugs, so that management is increasingly complex, and requires high costs because of the magnitude of the risks that must be borne. The risks that must be experienced are storage costs, booking costs, damage costs, higher number of expired drugs and the possibility of patients getting drugs that are not optimal in doctor's prescribing, impacting by decreased quality and quality of health service. This research aims to find out the description of the suitability of prescription writing with hospital formulary on outpatient general patients in the Hospital